The effect of black barberry hydroalcoholic extract on immune mediators in patients with active rheumatoid arthritis: A randomized, double–blind, controlled clinical trial. (10th September 2020) - Aryaeian, Naheed; Hadidi, Mahsa; Mahmoudi, Mahdi; Asgari, Marziyeh; Hezaveh, Zohreh Sajadi; Sadehi, Sara Khorshidi
Abstract : Rheumatoid arthritis (RA) is an autoimmune disease associated with inflammation. In this trial, we aimed to investigate the Immunomodulatory effect of hydroalcoholic extract of black barberry on immune mediators in patients with active rheumatoid arthritis. In this randomized, double–blind, placebo‐controlled clinical trial, 80 women with active RA were randomly assigned into two groups of two capsules, each containing 1, 000 mg black barberry extract ( n = 40) or maltodextrin placebo ( n = 40) daily for 12 weeks. Demographic indices, physical activity, dietary intake, and disease activity were investigated using suitable questionnaires. Concentration of cytokines IL‐2, IL‐4, IL‐10, and IL‐17 in blood sample were measured using PBMC method. Statistical analysis was performed using SPSS (version 22). At baseline, there were no differences between the two groups in terms of demographic indices, physical activity, and dietary intake ( p > .05). Black barberry supplementation reduced the severity of RA. It showed no significant effect on IL‐2 and IL‐4 cytokines ( p > .05). IL‐17 levels decreased significantly after the intervention within the black barberry group, while IL‐10 had a significant increase in this group ( p < .05). Barberry extract may reduce inflammatory and increase anti‐inflammatory cytokines in RA, and stimulates the immune response by increasing Th2 production.